From populist developmentalism to liberal neodevelopmentalism: The specificity and historical development of Brazilian capital accumulation - Grinberg, Nicolás (2016)
This article analyses the trajectory of Brazilian society between the time of populist developmentalism and the emergence of neo-developmentalism. Challenging mainstream accounts, it argues that the various policy regimes consolidating and disappearing throughout the period have been forms of realisation of the autonomously regulated process of capital accumulation on a global scale. More concretely, it is claimed that Brazilian capitalism has developed under a specific form which sprung from its particular original subsumtion in the international division of labour as producer of primary commodities; capital has accumulated there through the recovery of a portion of the local ground-rent. This form of capital accumulation has come about through specific developmental patterns, state policies, and political processes. Analysis of the historical development of the Brazilian process of capital accumulation demonstrates the inherent unity amongst the various policy regimes.